METAFORA PEREMPUAN DALAM NOVEL JATISWARA KARYA LALU AGUS FATHURRAHMAN: - Marlina; Saharudin; Aswandikari (Universitas Hamzanwadi, 2026)
This study, entitled Metaphors of Women in the Novel Jatiswara by Lalu Agus Fathurrahman, is based on the view that literature serves as both a cultural reflection and a medium for constructing values, including the representation of women. Jatiswara was selected because it presents rich symbolizations of women within the cultural context of the Sasak community. The purpose of this research is to describe the forms of women’s metaphors and to reveal the representation of Sasak women’s feminism in the text. The study employs a qualitative method using Lakoff and Johnson’s conceptual metaphor theory and the feminist concepts of the good woman and the new woman. The findings indicate three main categories of women’s metaphors: structural, ontological, and orientational. The representation of Sasak women’s feminism demonstrates ambivalence—women are portrayed as good women, who are noble and moral guardians, and as new women, who are critical, independent, and progressive). This research contributes to the development of conceptual metaphor studies and local feminism within Indonesian literary scholarship.